Transcriptomics Integrated With Widely Targeted Metabolomics Reveals the Mechanism Underlying Grain Color Formation in Wheat at the Grain-Filling Stage - Li, Li; Kong, Zhiyou; Huan, Xiuju; Liu, Yeju; Liu, Yongjiang; Wang, Qianchao; Liu, Junna; Zhang, Ping; Guo, Yirui; Qin, Peng (Frontiers in Plant Science, 2021)
Colored wheat grains have a unique nutritional value. To elucidate the color formation mechanism in wheat seeds, comprehensive metabolomic and transcriptomic analyses were conducted on purple (Dianmai 20-1), blue (Dianmai 20-8), and white (Dianmai 16) wheat at the grain-filling stage. The results showed that the flavonoid biosynthesis pathway was closely related to grain color formation. Among the 603 metabolites identified in all varieties, there were 98 flavonoids. Forty-six flavonoids were detected in purple and blue wheat, and there were fewer flavonoids in white wheat than in colored wheat. Integrated transcriptomic and metabolomic analyses showed that gene expression modulated the flavonoid composition and content, resulting in different metabolite levels of pelargonidin, cyanidin, and delphinidin, thus affecting the color formation of wheat grains. The present study clarifies the mechanism by which pigmentation develops in wheat grains and provides an empirical reference for colored wheat breeding.